Analisis Penggunaan Bahasa Dalam Konten Iklan Produk Kencantikan The Originote Di Media Sosial Tik Tok - Fazan Akbar Ridhani; Agil Rismawan (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2025)
The original aim of this research was to find out and identify language errors in advertising content on general media, especially Tiktok. Tik Tok public media is a popular platform for marketing products, including beauty products. The research results show that THE ORIGINOTE uses various language strategies to attract consumer attention and interest, such as the use of positive and emotional terms, slang and humor. THE ORIGINOTE also creates a brand image of a product that is natural, safe and effective. The author uses a qualitative research approach. The data used in this research are posts containing product advertisements that have language errors in the caption. The data source in this research is posts from the official account @theoriginote. The data collection technique used is observation and documentation in the form of screen captures, while the analysis technique is qualitative narrative. What will happen in this research are several language errors, among which the most frequently found are the use of foreign languages ​​(slang) together with Indonesian, punctuation errors, inappropriate use of capital letters, and the use of non-standard terms.